Pembuatan Aplikasi Reservasi Dokter Praktek Di Apotek ACP Ambon Berbasis Web Dan Android - Reyviano Marcyan Luhulima; Justinus Andjarwirawan; Yulia Yulia (Jurnal Infra, 2017)
ACP Ambon pharmacy is one of the largest pharmacy in Ambon City. In this Pharmacy in order to reserve the doctor, the patient needs to come first to the pharmacy and register their name. If the patient gets a large queue number, they prefer to go home and come back later. However, it is very inefficient and wasting time. Moreover, when the patient returns to the pharmacy, their queue number have been passed so the patient has to wait until the last number of queue if they want to be served. In addition, in the making process of patient medical records and prescription which are using a paper also often causes some problems. In an example, patient’s medical records and prescriptions can be lost or damaged, and the process of recording the patient's medical record and prescription becomes more difficult. Thus, it needs a doctor reservation application by integrating between website technology with Android-based smartphone.This application is created by using HTML, PHP, JavaScript, and MySQL database programming language on a web-based application. Java programming languages and SQLite databases are on Android based apps. Bootstrap template is used as the display of the application. The notification feature of patient’s queue numbers on Android-based apps used Firebase Cloud Massaging (FCM).The end of the result of this application development are to be able to process the doctor’s reservation quickly, received notification of queue number of other patients that are being examined by doctor, record the patient’s medical record and prescription with computerized. The owner can also see the doctor's daily check